TOURISM DESTINATION PROMOTION THROUGH SOCIAL MEDIA : A CONTENT STUDY OF DMO GORONTALO - Kusuma, Citra Aditya; Ismail, Yulinda L; Hariyanti, Fina (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
The promotion of tourism destinations via social media has significantly increased in the contemporary tourism industry. This paradigm shift is driven by advancements in information technology and the growing utilization of social media platforms. However, in Gorontalo region, particularly in Tomini Bay area, social media has not been fully leveraged by the Destination Marketing Organization (DMO) to market the region’s potential tourist attractions. Therefore, this study aims to evaluate the promotional content of tourism destinations in Tomini Bay area by the DMO on social media platforms, specifically Facebook and Instagram, as well as to understand tourists’ perceptions and responses to these promotional strategies. The research employs a mixed-method approach through content analysis and online surveys. The findings provide in-depth insights into the promotional strategies employed by DMO’s Gorontalo, tourists’ responses to these strategies, and recommendations for enhancing effective tourism promotion strategies. The study reveals that social media has not been utilized consistently and optimally by DMO Gorontalo which impacting the achievement of its tourism promotion objectives. To improve the effectiveness of tourism promotion strategies, several aspects need to be addressed, including: (1) consistency and frequency of promotional content uploads; (2) diversification of promotional content; and (3) optimization of user-generated content.